2021
DOI: 10.1016/j.plabm.2021.e00207
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of spexin and adiponectin may predict insulin resistance in patients with non-alcoholic fatty liver

Abstract: Adipose tissue is endocrine organ that responds by secreting numerous hormones that regulate metabolism in skeletal muscle and the liver. The aim of this study was to compare the levels of spexin and adiponectin in patients with non-alcoholic fatty liver and evaluate the relationship between circulating adipocytokines and insulin resistance. Two groups of subjects were evaluated: 41 non-alcoholic fatty liver subjects (age 35.17 ​± ​12.29 year, BMI 30.97 ​± ​2.75 ​kg/m2) and 38 normal controls (age 38.47 ​± ​11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A similar phenomenon of increased β-Klotho has also been observed in adiponectin-mediated FGF21 improvement of blood glucose [106]. Another study revealed that adiponectin, as a downstream effector of FGF21, enhances Akt activation and promotes glucose clearance in the soleus and gastrocnemius muscles of mice because adiponectin is one of the sensitizing regulators of insulin [106,107]. The enhanced insulin sensitivity observed with FGF21 treatment has been attributed to its biological property of acting as a signal transduction terminal for exogenous substances to improve insulin signaling.…”
Section: Fgf21 Preserves Muscle Glucose Metabolism In An Insulin-depe...mentioning
confidence: 58%
“…A similar phenomenon of increased β-Klotho has also been observed in adiponectin-mediated FGF21 improvement of blood glucose [106]. Another study revealed that adiponectin, as a downstream effector of FGF21, enhances Akt activation and promotes glucose clearance in the soleus and gastrocnemius muscles of mice because adiponectin is one of the sensitizing regulators of insulin [106,107]. The enhanced insulin sensitivity observed with FGF21 treatment has been attributed to its biological property of acting as a signal transduction terminal for exogenous substances to improve insulin signaling.…”
Section: Fgf21 Preserves Muscle Glucose Metabolism In An Insulin-depe...mentioning
confidence: 58%
“…10 Similar to the findings of animal studies, plasma SPX levels were lower in NAFLD patients compared to controls. 59 These findings demonstrate a potentially therapeutic value of SPX for hepatic steatosis/NAFLD treatment.…”
Section: Protective Effect Of Spx On Nafldmentioning
confidence: 77%
“…However, the level of spexin in the DM-OB group was significantly lower than that in the DM-OV group and DM-NW group. Previous studies have shown that serum spexin levels are significantly lower in patients with T1DM, T2DM, gestational diabetes mellitus, obesity, polycystic ovarian syndrome and nonalcoholic fatty liver disease (6,(11)(12)(13)(14)(15). Previous studies have found that the expression of spexin changes when diseases progress.…”
Section: Discussionmentioning
confidence: 99%